The effect of foreign direct investment spillovers on the performance of food and baverage industries in indonesia using stochastic frontier analysis - Karari Budi Prasasti; Dyah Wulan Sari; Rossanto Dwi Handoyo (INOVASI, 2022)
This study examine the spillovers effect of foreign direct investment to productivity of food and baverage industries in Indonesia using firm-level panel data covering 5.581 firms and 29.890 observations. The data were analysis using a stochastic frontier approach. The foreign share variable in the inefficiency equation has a statistically significant effect and show a negative relationship. That means foreign companies are more efficient than domestic companies. This is because foreign companies in Indonesia have a large scale and more advanced on technology in the production process. The horizontal spillover coefficient show a significant effect with a negative sign on the inefficiency function. However foreign companies cause domestic companies to be more efficient in the same industries. The competition of foreign and domestic companies make domestic companies will increase production optimally.